The new Socrates: parrhesia and epimeleia heautou based on the position of rappers (2019)
This text addresses philosophy as a thought experiment, according to Larrosa, Masschelain, and Kohan. The socratic notions of parrhesia and epimeleia heautou are discussed on the basis of Foucault's Hermeneutics of the Subject; and the practice of parrhesia as a philosophy is discussed based on The Government of Self and Others, in order to establish a dialogue with the voices from the streets: rappers. It is argued that they are the new Socrates. The possible dialogues between city and education are analyzed. A reflection is developed on young people's political experience, given that Socrates frequented the Agora because he perceived political participation as a duty. He took care of himself to help others take care of themselves, which is a responsibility. To support the claim that rappers are the new Socrates, the language of the streets is drawn from interviews.